A Study on Factors Influencing the Job Satisfaction of Bank Employees in Nepal (With special reference to Kathmandu, Lalitpur, and Bhaktapur District) - Neupane, Bashu (NCC Journal, 2019)
Job satisfaction means the positive feeling or attitude that employees have towards their job, which acts as a motivation to work. It is a combination of emotion, belief, feeling, sentiment, and other allied behavioral tendencies. This study is focused on analyzing the job satisfaction of banking employees on the basis of the working environment, cooperation among employees, training and promotion and salaries. Employees of Nepalese commercial banks were selected using a convenience sampling method for the study. A total of 112 respondents were selected to sample the employees of banks located in Kathmandu, Lalitpur, and Bhaktapur. The descriptive, as well as analytical research designs were used to analyze and draw a conclusion about the job satisfaction of bank employees. The self-structured questionnaire has been used. The major influencing factors for job satisfaction were salary, followed by training and promotion, working environment, and cooperation among them.